The quality and safety culture in general hospitals: patients', physicians' and nurses' evaluation of its effect on patient satisfaction. (21st June 2018) - Kagan, Ilya; Porat, Nurit; Barnoy, Sivia
Abstract: Objective: To explore the disparities between patients' and health care workers' perception of the quality and safety culture and to explore the relationship between patient perceptions, and engagement in, and satisfaction with their care and treatment. Design: A cross-sectional study was conducted in medical–surgical wards of four Israeli general hospitals. Data were collected using a self-administered questionnaire. Setting: Fourteen medical–surgical wards of the four hospitals where data were collected. Participants: The sample comprised of 390 physicians and nurses and 726 inpatients admitted for at least 3 days. Main outcome measures: A self-administered questionnaire that covered the following topics: (i) quality and safety culture, (ii) patient engagement, (iii) patient satisfaction, (iv) an assessment of the care quality and safety in the ward and (v) sociodemographic data. The questionnaire was translated into Arabic and Russian. Sixty nine items were directed to the staff and 71 to patients. Results: Patients evaluated the quality and safety culture significantly higher than did the health care workers. Significant correlations were found between patients' engagement in and satisfaction with their care and their quality and safety assessments. Their evaluation of this culture was the only predictor of their satisfaction and engagement. Arabic-speaking patients rated four variables, including patients' satisfaction with their care, lower than did Hebrew and Russian speakers. Conclusions: Patients have sufficient experience and understanding to form an opinion of the quality and safety of their care. The lower evaluation of the quality and safety culture expressed by health care workers might stem from their more realistic expectations.